PATTERNS OF ANTIBIOTIC PRESCRIPTION FOR THE TREATMENT OF URINARY TRACT INFECTIONS IN KOTARAJA PUBLICAL CENTER - Dehi, Rosita Irianti; Maya Permatasari; Marselino F. Paepadaseda (Pusat Riset dan Inovasi Nasional, 2022)
Urinary Tract Infection (UTI) is an infectious disease that is often found in general practice. Urinary tract infection (UTI) can be defined as the presence of bacteria in the urine where these bacteria may invade the tissues of the urinary tract. The type of research used in this research is descriptive research. This research was conducted in June 2021, in the medical records section of the Kotaraja Health Center, Jayapura City. The population in this study were all patients with UTI who were treated at the Kotaraja Publical Center in June - December 2020 with a total of 30 patients. The results showed that there were more female patients than male, namely 17 people (57%). most patients came from the age group 26-35 years as many as 11 people (37%). The most dominant type of antibiotic prescribed was ciprofloxacin in 24 patients (80%). The most dominant group of prescribed antibiotics was Fluroquinolone as many as 24 patients (80%). The most widely used dose of antibiotic preparations was Ciprofloxacin 500 mg for 24 patients (80%). The most frequent duration of antibiotic administration was 5 days for ciprofloxacin as many as 20 patients (67%). Conclusion: The most frequently used antibiotic at the Kotaraja Publical Center is Ciprofloxcacin